Evaluation of the Sealing Ability and Bond Strength of Two Endodontic Root Canal Sealers: An In Vitro Study - Manuel Marques Ferreira; José Pedro Martinho; Inês Duarte; Diogo Mendonça; Ana Catarina Craveiro; Maria Filomena Botelho; Eunice Carrilho; Carlos Miguel Marto; Ana Coelho; Anabela Paula; Siri Paulo; Nuno Chichorro; et al. (MDPI AG, 2022)
Background: Obturation represents a critical step in endodontic treatment, which relies on a core material and a sealer. This study aims to evaluate the sealing ability and bond strength to the root canal walls of an epoxy resin-based sealer (AH-Plus®, Dentsply Sirona, Johnson City, TN, USA) and a bioceramic sealer (GuttaFlow Bioseal®, Coltène/Whaledent, GmbH + Co. KG, Langenau, Germany). Methods: Thirty-eight maxillary anterior teeth with single roots and identical round sections were separated into two experimental groups according to the root canal sealers used, namely, G1 = AH-Plus® and G2 = GuttaFlow Bioseal®, and two control groups, specifically, G3 = the negative control and G4 = the positive control. The sealing capacity was measured by the penetration of the radioactive isotope 99mTc. For the push-out test, the compressive force test was performed in a universal machine and the force was applied by exerting pressure on the surface of the material to be tested in the apical to the coronal direction and using three test points with different diameters. Results: GuttaFlow Bioseal® exhibited superior sealing ability compared to AH-Plus® (p = 0.003). Regarding the bond strength, AH-Plus® provided higher adhesion values than GuttaFlow Bioseal® in the three sections of the tooth root (p = 0.001). Conclusions: GuttaFlow Bioseal® had significantly better sealing ability than AH-Plus® but lower adhesion values in the three zones of the root canal, with statistically significant differences between the groups. However, it is important to note that for the action of endodontic sealers to be maximized, the root-filling technique must be most appropriate.